Radiative forcing by light-absorbing aerosols of pyrogenetic iron oxides - Akinori Ito (Nature Portfolio, 2018)
Abstract Iron (Fe) oxides in aerosols are known to absorb sun light and heat the atmosphere. However, the radiative forcing (RF) of light-absorbing aerosols of pyrogenetic Fe oxides is ignored in climate models. For the first time, we use a global chemical transport model and a radiative transfer model to estimate the RF by light-absorbing aerosols of pyrogenetic Fe oxides. The model results suggest that strongly absorbing Fe oxides (magnetite) contribute a RF that is about 10% of the RF due to black carbon (BC) over East Asia. The seasonal average of the RF due to dark Fe-rich mineral particles over East Asia (0.4–1.0 W m−2) is comparable to that over major biomass burning regions. This additional warming effect is amplified over polluted regions where the iron and steel industries have been recently developed. These findings may have important implications for the projection of the climate change, due to the rapid growth in energy consumption of the heavy industry in newly developing countries.